2021
DOI: 10.3390/buildings11050199
|View full text |Cite
|
Sign up to set email alerts
|

Determining Critical Success Factors for Public–Private Partnership Asset-Backed Securitization: A Structural Equation Modeling Approach

Abstract: Public–private partnership (PPP) has been widely applied in China and many developing countries in the recent decade. As new PPP projects gradually enter the operational phase, the issue of refinancing becomes increasingly important. PPP–ABS plays an indispensable role in PPP project refinancing. The factors that promote the success of the emerging PPP–ABS in the China financial market need to be determined. To accomplish two objectives, namely, to identify critical success factors (CSFs) and to explore the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…Their research highlighted the importance of supporting institutional systems and market factors for PPP-ABS [13]. Liu et al (2021) determined the critical success factors for PPP-ABS through a questionnaire survey and adopted structural equation modeling to explore the relationship between these factors and the success of PPP-ABS. The results showed that the maturity of relevant institutions, including transparent information disclosure, mature accounting and tax standards, mature secondary market, clear and effective government regulation, will affect the issuance and success of PPP-ABS [12].…”
Section: Related Studies Of Ppp-absmentioning
confidence: 99%
See 1 more Smart Citation
“…Their research highlighted the importance of supporting institutional systems and market factors for PPP-ABS [13]. Liu et al (2021) determined the critical success factors for PPP-ABS through a questionnaire survey and adopted structural equation modeling to explore the relationship between these factors and the success of PPP-ABS. The results showed that the maturity of relevant institutions, including transparent information disclosure, mature accounting and tax standards, mature secondary market, clear and effective government regulation, will affect the issuance and success of PPP-ABS [12].…”
Section: Related Studies Of Ppp-absmentioning
confidence: 99%
“…However, with the rapid promotion of PPP, many problems have been exposed, that are not conducive to its sustainable development [8,9]. ABS can improve the liquidity of basic assets [10,11], which can activate the existing PPP project assets [12][13][14][15]. By the end of 2016, the PPP-ABS was officially proposed in China.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, through a measurement model and a structural model, SEM is an effective methodology for assessing model constructs and hypothesized structural relations among latent factors [74]. Thus, SEM has been widely used in the field of construction management, e.g., [58,[75][76][77][78][79][80]. The structural model can be developed and analyzed further after the measurement model has been evaluated satisfactorily [65].…”
Section: Sem Approachmentioning
confidence: 99%
“…In order to ensure the standardization and unity of a large amount of relevant index data, data preprocessing measures need to be taken to prepare for the screening of indicators in random forest model. e data standardization processing is shown in equations ( 1)- (3).…”
Section: Audition and Data Processing Of Credit Risk Assessmentmentioning
confidence: 99%
“…The stadiums and gymnasiums operated by the government after the game cannot produce good social benefits and even become idle buildings because of the single function, low actual utilization rate and the operation mode do not meet the market demand. This situation undoubtedly increases the financial burden of the local government and fails to achieve the purpose of making full use of social resources [ 3 ]. Therefore, combined with past cases and experience, the construction and management of sports public service venues has produced a form of cooperation between the government and social capital, namely PPP mode.…”
Section: Introductionmentioning
confidence: 99%